Penyuluhan Pencegahan Cacingan Pada Siswa Madrasah Ibtidaiyah Islahul Muta’alim di Kota Mataram - Yanuar, Rinta Putri; Neneng Rachmalia Izzatul Muchlishah; Syauzatta Amani; Tity Afriliani; Zulfia Ika Indriani (Universitas Mataram, 2024)
The prevalence of worm infections among elementary school children in West Nusa Tenggara reaches 13.1%. Worm infections can disrupt children's growth and immune system, and in the long term, this condition can cause cognitive impairments in children. Changing lifestyles and improving environmental sanitation are crucial steps in preventing worm infections in children. However, awareness and action toward these measures remain low due to insufficient knowledge about them. The objective of this education is to raise awareness and knowledge about the dangers of worm infections and how to prevent them. The methods used in this activity include education on worm infection prevention and demonstrations of proper handwashing techniques. Students at Islahul Muta'alim Elementary Madrasah showed good enthusiasm during the activities, which facilitated smooth implementation. It is hoped that these activities will enhance students' understanding of worm infections.